The Dynamic Impact of the Tiger within Chinese Martial Arts - Wing Lam; Saleem Alamudeen (Universidad de León, 2012)
In Asia, there is, in general, a great reverence held for the tiger. The tiger has been imitated and reigns supreme as king of all the beasts throughout Asia. The relationship between man and tiger holds a strange duality in that as much as the tiger is feared for its fierce savagery and destructive power, it is also revered for these very same qualities and for its majestic nature. Therefore, the very symbolic essence of the tiger has permeated all levels of the Asian community and culture; art, mythology, religion, astrology, herbology, and military fighting strategies. The purpose of this article is to show the many rich aspects that the tiger exhibits, and its influence and impact on Asian culture and Chinese martial arts in particular. Martial arts such as Cantonese Hung Gar (Hong Family) and Hasayfu Hung Gar (Hong Family Four Lower Tigers) dedicate a portion of their systems to achieving awesome strength and speed, and to imitating the tiger's physical prowess. By doing so, they may achieve higher levels of effectiveness within the martial arts.